Aspek Hukum Import Sampah Plastik - Solikah Ana Estikomah (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2019)
Indeveloped countriesbannedtoxic waste began to be recorded afterproved disastrous. In addition there isa gap for the cost of treating waste plastic in the developed countries anddeveloping countries. The high cost ofwastewater treatmentin plastic developed countries in part due to the high cost of compliance and strict law. In contrast, the low cost sewage treatment plastic in developing countriesdue to the lack of law enforcement. On the other hand, as a result of the construction waste requires complextechnology for processing and finaldisposal of hazardous materials is increasingly narrows with increasingawareness of the importance ofenvironmental protection. Waste-producing countries plastic and then look for the easiestand cheapest way to dispose of waste. Poor countries thatare developing targeted for regulation lingkungannnyastill weak. The existence of import export plastic waste between advanced and developing countries may be said to have lastedlong enough for the re-emergence of international public awareness of thedangers of pollution is industrial waste. The analysis research was conducted in a juridical-normative manner based on literature studyKeywords: Waste, law, plastic, import